Status of ram spermatozoa DNA after freeze-drying process - Takdir Saili; wahono Esthi Prasetyaningtyas; Mohamad Agus Setiadi; Srihadi AgungPriyono; Arief Boediono (Indonesian Center for Animal Research and Development (ICARD), 2006)
The process of freeze drying caused detrimental effect on plasma membrane and acrosome of the spermatozoa, even it potentially could alter the chromatin and DNA integrities. On the other hand, DNA integrity is essential for spermatozoa to participate in pronucleus formation during fertilization event. Therefore the evaluation of DNA integrity should be carried out to study the effect of freeze drying process. EDTA, EGTA, and PBS were used as dilution media of spermatozoa prior to freeze drying process to protect the DNA. Toluidine blue staining and comet assay methods were used to evaluate the alteration on chromatin and DNA integrities of spermatozoa, respectively. The results revealed that the highest compacted chromatin after 6 months storage of freeze-dried spermatozoa were observed from EGTA-3 (98%) and EGTA-1 (97%) treatments that had significant differences compared to all PBS treatments (90-92%), but not for fresh spermatozoa (100%). Whereas, the highest compacted DNA integrity of freeze-dried spermatozoa were observed from EGTA-2 (92%) and EGTA-3 (92%) but had no significant differences compared to other treatments including fresh spermatozoa (97%). These results demonstrate that EDTA and EGTA tend to be able to protect chromatin and DNA integrities of ram spermatozoa during freeze-drying and storage compared to PBS. Key Words: Freeze-Drying, Spermatozoa, DNA, Toluidine Blue, Comet Assay